Disaster preparedness in vulnerable rural communities: Integrating preparedness index and demographic variables in a post-landslide context - Aziz, Muhammad Hilmy; Azzamullah, Aziz (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Landslides are natural disasters that often result in significant human and material losses, especially in areas with unstable topography. In Jombang Regency, East Java, a major landslide occurred on January 28, 2014, killing 14 people and destroying infrastructure. This study aims to examine the level of disaster preparedness among the local community of Kopen Hamlet in anticipation of future landslides. Methods: This research employed a quantitative approach using survey and interview methods to collect primary data. A preparedness index was used to measure the readiness level of residents, while the Kolmogorov-Smirnov method was applied to test the normality of the data distribution based on demographic variables such as gender, age, and education. Findings: The study found that 68% of respondents were classified as sufficiently prepared, and 69% were nearly prepared depending on demographic factors. The Kolmogorov-Smirnov test yielded an Asymp. Sig (2-tailed) value of 0.063, indicating that the data were normally distributed. Preparedness levels were relatively consistent across different community groups. Conclusion: The results highlight the importance of demographic factors in community disaster preparedness and provide a foundation for targeted risk reduction interventions in similar vulnerable areas. Novelty/Originality of this article: This study uniquely integrates a preparedness index with demographic analysis in a post-disaster context, offering empirical insights from a localized rural community that has received limited prior research attention in Indonesian landslide risk studies.